2021
DOI: 10.3390/ijerph182010676
|View full text |Cite
|
Sign up to set email alerts
|

Are Sleep Problems Related to Psychological Distress in Healthy Aging during the COVID-19 Pandemic? A Review

Abstract: The SARS-CoV-2 pandemic, characterized by home confinement and other restrictive measures to reduce the spread of the infection, led to significant changes in people's habits and lifestyle. One of the most common problems is the worsening of sleep quality or quantity, which could have negative effects on psychological wellbeing, particularly in older adults. The purposes of the present literature review considering healthy aging subjects are (a) to examine the existing research on sleep alterations during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 104 publications
2
11
0
Order By: Relevance
“…4,32 Finally, distress factors such as loneliness and anxiety, as well as the NPS itself, such as aggravating depression and anxiety, may also result in sleep disorders due to the covid-19 lockdown in patients. 43 It was observed that the worsening in NPS (especially anxiety) during quarantine was much greater in patients with mild dementia than in those with advanced dementia. 44 One possible explanation for this may be that subjects with relatively mild dementia may have undergone more radical changes in their lifestyle habits during quarantine than those with severe dementia, who are generally more home-bound and less active.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,32 Finally, distress factors such as loneliness and anxiety, as well as the NPS itself, such as aggravating depression and anxiety, may also result in sleep disorders due to the covid-19 lockdown in patients. 43 It was observed that the worsening in NPS (especially anxiety) during quarantine was much greater in patients with mild dementia than in those with advanced dementia. 44 One possible explanation for this may be that subjects with relatively mild dementia may have undergone more radical changes in their lifestyle habits during quarantine than those with severe dementia, who are generally more home-bound and less active.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the rapid cognitive deterioration in people living with dementia during the pandemic, the inability of these patients to adapt to new living conditions, and the inability of patients to continue their usual daily activities, may have led to the development of apathy and triggered depression 4,32 . Finally, distress factors such as loneliness and anxiety, as well as the NPS itself, such as aggravating depression and anxiety, may also result in sleep disorders due to the covid‐19 lockdown in patients 43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability can be due to several aspects, such as the age category among the elders, as the younger group among older adults (60–70 years old) seems to have had the greatest impact on sleep ( Emerson, 2020 ). A review of sleep patterns and mood associations in older adults during the pandemic found many studies that reported important changes in sleep during this period, but also a few studies that found no changes in sleep in this population ( Cipriani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese population is aging at an unprecedented pace, and older population aged over 65 years will reach 336 million by 2050, accounting for one-third of the total Chinese population ( National Bureau of Statistics of China, 2017 ; Zhong et al, 2018 ). Alongside the increased aging population, self-neglect is becoming a prominent problem that challenges healthy aging ( Cipriani et al, 2021 ; Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%